Tubule‐derived INHBB promotes interstitial fibroblast activation and renal fibrosis. Issue 1 (20th October 2021) - Sun, Yanyan; Cai, Huimin; Ge, Jia; Shao, Fang; Huang, Zhen; Ding, Zhi; Dong, Lei; Chen, Jiangning; Zhang, Junfeng; Zang, Yuhui
Abstract: Upstream stimuli for myofibroblast activation are of considerable interest for understanding the mechanisms underlying renal fibrosis. Activin B, a member of the TGF‐β family, exists as a homodimer of inhibin subunit beta B (INHBB), but its role in renal fibrosis remains unknown. We found that INHBB expression was significantly increased in various renal fibrosis models and human chronic kidney disease specimens with renal fibrosis. Notably, the increase of INHBB occurred mainly in the tubular epithelial cells (TECs). In vivo, inhibiting INHBB blocked the activation of interstitial fibroblasts and ameliorated the renal fibrosis induced by unilateral ureteral obstruction or ischemia–reperfusion injury, while ectopic expression of INHBB in the TECs was able to activate interstitial fibroblasts and initiate interstitial fibrosis. In vitro, overexpression of INHBB in TECs led to the secretion of activin B, thereby promoting the proliferation and activation of interstitial fibroblasts through activin B/Smad signaling. Furthermore, inhibition of activin B/Smad signaling attenuated the fibrotic response caused by tubular INHBB. Mechanistically, the upregulation of INHBB depended on the transcription factor Sox9 in the injured TECs. Clinical analyses also identified a positive correlation between Sox9 and INHBB expression in human specimens, suggesting the Sox9/INHBB axis as a positive regulator of renal fibrosis. In conclusion, tubule‐derived INHBB is implicated in the pathogenesis of renal fibrosis by activating the surrounding fibroblasts in a paracrine manner, thereby exhibiting as a potential therapeutic target. © 2021 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.